Effect of Light Spectra on Growth Performance and Immune Response of Koi Carp, Cyprinus carpio (Linnaeus, 1758) - Bairwa, Mukesh Kumar; Saharan, Neelam; Rawat, Kiran Dube; Tiwari, Virendra Kumar; Prasad, K. Pani (Fishery Technology, 2017)
The present study was undertaken to assess thegrowth performance and non-specific immune responseof koi carp, Cyprinus carpio exposed to lightemittingdiodes (LEDs): blue (450 nm), green (530nm), yellow (530 nm) and red (630 nm) under longphotoperiod (16 h light) for 90 days. White fluorescentlight (simulated natural photoperiod, SNP) wasused as control. Growth performance of fish washigher (p